ICS teaching module on urodynamics for lower urinary tract symptoms in men - Sanjay Sinha; Tufan Tarcan; John Speich; Mauricio Plata; Enrico Finazzi-Agro; Marcus Drake (Continence)
Aims:: To present the body of evidence about the urodynamic assessment and diagnosis of male lower urinary tract symptoms (LUTS) and to serve as a scientific background review and evidence base for the presentation available on the International Continence Society (ICS) website on Urodynamics in male LUTS. Methods:: This teaching module was developed by the Urodynamics Committee of the ICS as a clinical practice tool. The module examines the indications, pre-test preparation, urodynamics technique, key findings, and interpretation, of urodynamics in adult men presenting with refractory voiding or storage LUTS. The module is based on evidence, clinical practice guidelines, existing ICS Standardization documents, and consensus formation by the members of the Working Group, and review by the members of the ICS Urodynamics and Standardization Steering Committees. The module is complemented by educational material on the ICS website. Results:: Invasive urodynamics should be considered in select men before surgery to quantify obstruction and the detrusor voiding contraction, as well as identify relevant storage abnormalities that might impact therapeutic strategy or prognosis. Initial evaluation frames the urodynamics question, informs technique, stratifies risk of infection, and provides input for interpretation of results. Adherence to the ICS standard technique of urodynamics and quality control, with clear annotations on the tracings, are crucial. Analysis includes scrutiny of the traces, and calculation of the ICS-Bladder Outflow Obstruction Index and ICS-Detrusor Contraction Index. When indicated, video-urodynamics can be used to locate the site of obstruction. Conclusion:: Urodynamics is useful in select men with LUTS and is usually offered only when invasive therapies are being considered. Combining information from urodynamics with clinical data is recommended.